Addressing the Gap in Reflective Teaching Practices: A Case Study of an English Lecturer in Non-English Major - Hasanah, Eni Uswatun; Suhatmady, Bibit; Asih, Yuni Utami; Kalukar, Ventje Jany; Iswari, Weningtyas Parama; Ping, Maria Teodora (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study explores the implementation of reflective teaching practices by an English lecturer instructing non-English major students and examines its contributions to professional development and classroom engagement. Reflective teaching involves a continuous cycle of self-assessment, adaptation, and improvement, which enables educators to refine their teaching methodologies to better meet students' needs. Using a qualitative case study approach, this research employed multiple data collection methods, including reflective journals, semi-structured interviews with the lecturer and students, and non-participant classroom observations. The findings indicate that reflective teaching significantly enhances lecturer self-awareness, fostering a more adaptive, student-centered instructional approach. By regularly analyzing his teaching methods and incorporating student feedback, the lecturer was able to create a more engaging and inclusive learning environment. Students reported increased motivation, participation, and comprehension as a result of these pedagogical adjustments. Even though the study found some benefits, it also found some problems that can make it hard to use reflective practices consistently. These problems include a lack of time and too much administrative work that should be done by the lecturer. The research underscores the importance of integrating reflective teaching into professional development programs to promote a culture of continuous learning among educators. Additionally, it highlights the need for further studies involving diverse educational settings to explore the long-term impacts of reflective teaching on both instructors and students. By addressing these gaps, future research can contribute to the development of more effective and sustainable approaches for incorporating reflection into higher education teaching practices